Schwa or Unstressed Vowel Sound in English Vocabulary Items from Surah Al-Baqarah of the Holy Quran - Wahyuni, Hanna Irma; Bram, Barli; Upor, Rose A. (Universitas Pendidikan Mandalika, 2024)
The schwa sound [É™] in the English language remains challenging and Â it appears to be overlooked by EFL learners. In practice, the word â€˜submitâ€™ is mispronounced by English learners: */sÊŒbËˆmÉªt/, instead of /sÉ™bËˆmÉªt/. Some studies have discussed schwa but their data sources were not the Holy Quran. Â Hence, this article investigated the schwa sound in English vocabulary items collected from the Holy Quran and represented by the letters 'o' and 'u' as in â€˜politeâ€™ and â€˜submitâ€™. Employing a descriptive qualitative method, the researchers collected 97 vocabulary items containing schwa sounds taken from surah Al-Baqarah verses 1-286. The results indicate that the schwa term that represents the unstressed syllable can be renewed with the terms proposed in this study such as 'astressed' and 'disaccented'. In addition, to maintain the schwa term, a change of its pronunciation is proposed becoming /ÊƒwÉ™/ and not /ÊƒwÉ‘Ë/. Most of the written vowels 'o' and 'u' are pronounced in a strong form, and unstressed vowels 'o' and 'u' are pronounced as a schwa. The appearance of unstressed schwa in the vowels 'o' and 'u' is not determined by its location whether it is in the first or second syllable. Schwa could appear anywhere as long as he was not stressed. Schwa was not found in stressed syllables. Lastly, all -ion [É™n] and -ous [É™s] suffixes must be pronounced with a schwa. The results imply that EFL learners ought to consult an excellent dictionary to ensure correct pronunciation. Future researchers are expected to examine further patterns of a schwa sound in English vocabulary items to assist EFL learners in improving their pronunciation.